Hetero-layered MoS2/C composites enabling ultrafast and durable Na storage - Li, Zhenyou; Klingeler, Rüdiger (Energy storage materials, 2019)
Transition metal dichalcogenides have been considered as promising conversion-type electrode materials in sodium ion batteries, which allow multi-electron redox processes providing high capacities. However, the conversion reaction often leads to dramatic structural degradation of the electrodes during de-/sodiation, which strongly limits their cycle lifetime, achievable capacities and rate performances. To circumvent these obstacles, in this study, we applied an interfacial engineering strategy by constructing a MoS2/C composite with an inter-overlapped hierarchical structure (MoS2-CC) through a bottom-up synthesis method. With the alternative stacking of MoS2 and carbon layers, MoS2-C@C provides an ideal environment to maintain the MoS2 structure through the van de Waals interaction within the multilayers. At the same time, the heterointerfaces in MoS2-C@C offer abundant electron transfer pathways. Consequently, the MoS2-C@C electrode exhibits prominently improved electrochemical performance including a high reversible capacity of 590mAhg−1, a superior cycling stability up to 1000 cycles and an excellent rate capability (164mAhg−1 at 20Ag−1 and 51mAhg−1 at 50Ag−1). The fast kinetics and high reversibility of the hetero-layered MoS2/C composite for Na storage demonstrate the feasibility of this synthetic strategy to prevent the structural degradation of the conversion-type battery materials.
Gesehen am 10.10.2019
Im Titel ist "2" tiefgestellt